A Tasmanian devil call encodes identity and decreases agonistic behaviour. Issue 6 (1st November 2020) - Davis, Kelly; Clarke, Jennifer A.
ABSTRACT: Tasmanian devils ( Sarcophilus harrisii ), the largest extant carnivorous marsupials, often congregate at carcasses when feeding, where they produce vocalisations onomatopoetically termed 'arffs'. Our aims were to quantify and determine: 1) arff acoustic structure, 2) if arffs are associated with feeding success, agonistic behaviours, and/or cooperation, c) if arffs encode identity. We observed 26 captive adults and measured the acoustic structure of 298 arff calls from 10 devils. Arffs are low amplitude, short duration, low frequency calls with tonal and harsh forms. During group-feeding events, increased utterances of arffs were associated with increased individual feeding success, decreased agonistic behaviours and increased cooperation ( n =  16 devils). Arffs increased when devils were tugging in synchrony on a large food item, apparently to reduce it into manageable portions. Thus, arffs may play a role in this form of by-product mutualism. We classified 90–91% of arffs to the correct individual (nine acoustic characteristics and PCA; n = 9 devils), indicating that arffs encode identity. Devil Facial Tumour Disease is transmitted through bite wounds from bitten to the biter. Tumours that form inside the mouths of infected devils, eventually causing death by starvation, may prevent devils from uttering recognisable arffs, resulting in them being bitten, thereby transmitting the disease.